The new rules of marketing & PR how to use social media, online video, mobile applications, blogs, news releases, and viral marketing to reach buyers directly - Scott, David Meerman (John Wiley & Sons, Inc., 2015)
"The pioneering guide to the future of marketing, The New Rules of Marketing & PR, has been updated and revised to retain its place as the top marketing and public relations book available. Learn the latest tools and techniques to communicate with buyers directly and in real-time, raise online visibility, and increase sales. For professionals, entrepreneurs, business owners, and professors alike, this one-of-a-kind guide offers actionable strategies that can be implemented immediately. In this completely revised and updated Fifth edition, David Meerman Scott offers fresh examples of success from organizations around the world ; delivers revised and expanded information on techniques like Inbound Marketing, Content Marketing, and Newsjacking; and offers the latest on social networks such as YouTube, Twitter, Facebook, Instagram, Snapchat, and LinkedIn. The New Rules of Marketing & PR gives you the inside track to gain attention for your product, service, or idea at a fraction of the cost of traditional marketing and PR programs."--Back cover
Includes bibliographical references and index. - Print version record and CIP data provided by publisher; resource not viewed
Keywords: Internet marketing; Public relations; Marketing sur Internet; Relations publiques; public relations; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior